2017
DOI: 10.2320/matertrans.m2017036
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study on Structural Relaxation Processes in Amorphous Germanium

Abstract: The structural relaxation of amorphous germanium was examined by molecular dynamics simulations based on the empirical Tersoff interatomic potential. Although the Tersoff potential overestimated both the melting and glass transition temperatures, it was able to reproduce the structural relaxation behavior. The potential energy decreases with thermal annealing below the glass transition temperature, but occasionally increases during structural relaxation. The mean square displacement of atoms also increases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Although this potential has a shortcoming in that it overestimates the melting temperatures of pure Si and Ge [26,27], it provides accurate cross-potential parameters that could be used to model the binary Si-Ge system. In addition, the availability of nucleation and growth for mixed SiGe clusters has been verified by Nordlund et al [28,29], and they have demonstrated that the Tersoff potential can effectively reproduce the structural properties of amorphous SiGe clusters.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…Although this potential has a shortcoming in that it overestimates the melting temperatures of pure Si and Ge [26,27], it provides accurate cross-potential parameters that could be used to model the binary Si-Ge system. In addition, the availability of nucleation and growth for mixed SiGe clusters has been verified by Nordlund et al [28,29], and they have demonstrated that the Tersoff potential can effectively reproduce the structural properties of amorphous SiGe clusters.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…It is also known that this potential can reproduce well-disordered structures, such as amorphous and liquid, and pressure-induced polyamorphism of group-IV elements. [28][29][30][31][32] The Ge atoms were initially arranged to take a diamondtype structure with a lattice parameter of 0.566 nm, which is consistent with the density of crystalline Ge. Here, the x, y, and z directions are defined as the [100], [010] and [001] directions of the diamond structure, respectively.…”
mentioning
confidence: 99%